Safety and efficacy of Levucell® SB (Saccharomyces cerevisiae CNCM I‐1079) as a feed additive for turkeys for fattening. (24th April 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Levucell ® SB when used in feed for turkeys for fattening. The additive is intended for use as a zootechnical additive (functional group: other additives) for the reduction of Salmonella contamination on carcasses through its decrease in faeces. In the context of a previous opinion, the identity of the strain was confirmed, and according to the Qualified Presumption of Safety (QPS) approach to safety assessment, it was presumed safe for the target species, consumers and the environment. Since no concerns are expected from other components of the additive, Levucell ® SB is also considered safe for the target species, consumers and the environment. The additive is not a skin or eye irritant or a skin sensitiser. Considering the data on the dusting potential, the user can be exposed to the additive by inhalation when handling it. The additive in non‐encapsulated form should be considered as a respiratory sensitiser. The coated formulation is not considered to pose a risk by inhalation. The efficacy of Levucell ® SB for the same purpose was previously established in chickens for fattening. The FEEDAP Panel concluded that there was some evidence that the addition of Levucell ® SB at 2 × 10 10 CFU/kg feed has a potential to aid the reduction of carcass contamination with Salmonella spp. Since the mechanism of action of the additive can be reasonably assumed to be same, Levucell ® SB can be presumed efficacious in turkeys for fattening at a dose of 2 × 10 10 CFU/kg feed without the need for additional studies.